2019
DOI: 10.1039/c9nr03424b
|View full text |Cite
|
Sign up to set email alerts
|

A nanopillar array on black titanium prepared by reactive ion etching augments cardiomyogenic commitment of stem cells

Abstract: The array highly efficiently promotes cardiomyogenic commitment of stem cells via integrin-mediated signalling compared to the smooth surface and is a potential platform for ex vivo differentiation of stem cells for cell therapy in cardiac tissue repair and regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…Consequently, bactericidal bTi has been introduced as a promising biomaterial for preventing IAIs. [ 48 ] To date, numerous studies [ 46,47,50 ] have focused on the biological properties of bSi and bTi surfaces, trying to optimize the dimensions of the pillars by changing one single processing parameter (i.e., etching time). It was reported that fine changes in the characteristics of the such etched structures may influence their biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, bactericidal bTi has been introduced as a promising biomaterial for preventing IAIs. [ 48 ] To date, numerous studies [ 46,47,50 ] have focused on the biological properties of bSi and bTi surfaces, trying to optimize the dimensions of the pillars by changing one single processing parameter (i.e., etching time). It was reported that fine changes in the characteristics of the such etched structures may influence their biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…28 Ti nano pillar surfaces, engineered by maskless plasma etching, were recently reported to promote both the osteogenic and cardiomyogenic lineage differentiation of mesenchymal stem cells. 31,32 In this context, it seemed attractive to analyze the potential osteoconductive properties of mechano-bactericidal Ti surface patterns established in our previous works. Here we aimed to investigate the adhesion, growth and differentiation ability of human adipose-derived mesenchymal stem cells (hASCs) in response to two types of mechano-bactericidal Ti topographies.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that increase in the surface roughness of biomaterials can effectively reinforce cell adhesion, thereby improving the effectiveness of engineered scaffolds. Many biocompatible compounds, such as polyurethane acrylate, [ 10a ] polylactic acid (PLA), [ 34 ] hydroxyapatite (HAp), [ 35 ] titanium (Ti), [ 36 ] and polydimethylsiloxane (PDMS) [ 37 ] have been developed to fabricate or modify biomaterial surfaces to determine cell morphology, adhesion, and metabolism for orienting cell differentiation. For instance, Yang et al.…”
Section: Biophysical Cues Of Biomaterials For Regulating Stem Cell Behaviormentioning
confidence: 99%
“…Various organic macromolecular polymers have been exploited for the development of pillar structures, such as PLA, [ 34 ] polycaprolactone (PCL), [ 50 ] and polystyrene (PS). [ 51 ] Biomaterials with pillar‐like characteristics have already been developed to investigate their effects on stem cells, including MSCs, [ 36 ] human adipose‐derived stem cells (hADSCs), [ 34 ] hematopoietic stem cells, [ 45 ] embryonic stem cells (ESCs), [ 51 ] and human neural stem cells (NSCs). [ 52 ] Pillars with high AR from the nanoscale to the microscale are inclined to reduce cell spreading but enhance elongation and differentiation.…”
Section: Biophysical Cues Of Biomaterials For Regulating Stem Cell Behaviormentioning
confidence: 99%
See 1 more Smart Citation